2022
DOI: 10.1371/journal.pone.0275387
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 pandemic on professional identity development of intern nursing students in China: A scoping review

Abstract: Purpose Clinical experience plays a vital role in the development of the professional identity (PI) of nursing students. China has applied a strict zero- COVID health policy in combating the COVID-19 pandemic since December 2019 and studies have been conducted in different places of China to explore PI development of nursing students during the pandemic time among the intern nursing students who are on clinical practices. This review study aims to synthesize the previous studies and provide a comprehensive pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…However, the image of heroism hides daily, mundane, dirty and gendered nursing work [ 42 ]. The praise and enthusiasm for nursing during COVID-19 may quickly fade away and may not result in profound impacts on the recruitment of nursing students according to the same phenomenon that occurred during the 2003 severe acute respiratory syndrome outbreak [ 43 ]. Politicians and policy-makers should turn their appreciation of nurses into positive actions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the image of heroism hides daily, mundane, dirty and gendered nursing work [ 42 ]. The praise and enthusiasm for nursing during COVID-19 may quickly fade away and may not result in profound impacts on the recruitment of nursing students according to the same phenomenon that occurred during the 2003 severe acute respiratory syndrome outbreak [ 43 ]. Politicians and policy-makers should turn their appreciation of nurses into positive actions.…”
Section: Discussionmentioning
confidence: 99%
“…La práctica avanzada de enfermería se refiere al desarrollo de competencias complejas que fortalecen tanto el desarrollo de la profesión de enfermería como la mejora de la atención brindada al paciente (Faterström, 2012). Aunque normalmente es realizada por enfermeras con una larga trayectoria profesional y niveles académicos superiores al grado, la pandemia de COVID-19 ha obligado a los internos de enfermería a asumir tareas avanzadas de cuidado sin estar completamente capacitados (Luo & Mao, 2022).…”
Section: Contextualización Del Problemaunclassified
“…In addition, emotional ups and downs were heightened by witnessing patients infected, quarantined and dying in front of them [ 12 ]. Their compassion fatigue may not be apparent; however, it may later affect the quality of nursing and even the development of professional identity [ 13 , 14 ]. Furthermore, Stamm suggested that the presence of vulnerability factors (such as a lack of social support) and personal strengths (such as resilience) may explain the development of compassion fatigue [ 15 ].…”
Section: Introductionmentioning
confidence: 99%